Corrosion in Crude Oil Distillation Units (CDUs) and a Study of Reducing Its Rates by Changing Chemical Injection Sites - shatab, Samer N.; Khudair, Wissam S.; Mohammed, Mohammed A.; Kahthim, Majid A. (Journal of Petroleum Research and Studies, 2023)
The injection of chemicals is one of the most important treatment steps used to reduce the effect of corrosion factors in crude oil distillation units in oil refineries. As a result of the availability of suitable conditions for the formation of the main corrosion agents, namely acids (HCI, H2S). It has become necessary to neutralize the effect of these factors in distillation units and towers by changing the sites of adding chemicals, where oil refineries use anti_ corrosion film and caustic soda (NaOH) as well as neutral amine to control and limit the effect of chloride ion, iron rates, salts and the (PH) values. As a result, the research paper is interested in developing a study of adding and changing chemical injection areas (points) of adding chemicals, especially (caustic soda and neutralizer amine) at different specific points, and as it is well known, crude oil passes through a number of different heat exchangers to raise its temperature in preparation for refining. It was found that changing the addition of the neutral amine in the striper tower area of the kerosene section (drops that are returned to the main refinery tower) has a significant effect in controlling the stabilization of pH values between (5.5-6.5) and reducing the iron ion concentration at a rate of (1% ppm), While the injection of caustic soda depends on the temperatures of the crude oil, so it is changed into two lines. The first is before the heat exchangers, that is, when the temperature of the crude oil is (20-35) c̊, and the second line is after the crude oil reaches the temperature (65-90) c̊, it has a significant effect in reducing the concentration of the chloride ion at a rate of (1-5 ppm) present in the form of chloride salts dissolved in the crude oil.